2019
DOI: 10.1029/2018ja026202
|View full text |Cite
|
Sign up to set email alerts
|

The Hall Electric Field in Earth's Magnetotail Thin Current Sheet

Abstract: One of the most important properties of Earth's magnetotail thin current sheet (TCS) is that its current is predominantly contributed by magnetized electrons. The Hall electric field, normal to the TCS and generated by charge separation, is critical to the generation of this electron current as well as a dawn‐dusk asymmetry of the magnetotail, such as duskside preference of magnetic reconnection and related structures and phenomena. However, systematic investigation of the Hall electric field has so far been l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 74 publications
(86 reference statements)
6
36
0
Order By: Relevance
“…However, the Hall effect is the only mechanism that could produce dawn‐dusk asymmetry in the Hall‐A simulation, so that the Hall effect must be the reason to create higher dawnside plasma density in Hall‐A as well as the MHD‐EPIC simulations. Figure f shows that the average E z component of MHD‐EPIC‐A is stronger on the duskside, which is a key for the E × B drift explanation and is consistent with Lin et al (), Lu et al (), and Lu et al (). The MESSENGER data indicate slight proton pressure enhancement on the dawnside (Figure b), but our simulations do not show any significant preference of the proton pressure.…”
Section: Simulation Resultssupporting
confidence: 88%
“…However, the Hall effect is the only mechanism that could produce dawn‐dusk asymmetry in the Hall‐A simulation, so that the Hall effect must be the reason to create higher dawnside plasma density in Hall‐A as well as the MHD‐EPIC simulations. Figure f shows that the average E z component of MHD‐EPIC‐A is stronger on the duskside, which is a key for the E × B drift explanation and is consistent with Lin et al (), Lu et al (), and Lu et al (). The MESSENGER data indicate slight proton pressure enhancement on the dawnside (Figure b), but our simulations do not show any significant preference of the proton pressure.…”
Section: Simulation Resultssupporting
confidence: 88%
“…Even so, in both magnetotail regions, these anisotropic electron currents can contribute to the stress balance in the current sheet (see discussion in Artemyev et al, ), and inclusion of these currents in current sheet models can help in description of very long (stretched) current sheet configurations (with weak gradients ∂ / ∂x and strong currents). This statistical result is confirmed by several case studies successfully comparing electron current density estimates derived from the pressure anisotropy and direct electron current measurements (see Figure in Artemyev et al, and Figure in Lu et al, ).…”
Section: Summary and Discussionsupporting
confidence: 62%
“…Furthermore, the average value of positive B z on the duskside (2.6 nT) is less than on the dawnside (3.6 nT), implying that the duskside magnetic field curvature radius is smaller and its current sheet is thinner (e.g., Büchner and Zelenyi, 1989; Rong ZJ et al, 2011). This thin current sheet is considered to be generated by a stronger Hall effect on the duskside (e.g., Lu S et al, 2019). Huang SY et al (2019) also suggested that the dawn–dusk asymmetry of KSMHs in the magnetotail could be caused by the Hall effect.…”
Section: Statistical Results and Analysismentioning
confidence: 99%